2013
DOI: 10.1063/1.4804380
|View full text |Cite
|
Sign up to set email alerts
|

Determination of stress, strain, and elemental distribution within In(Ga)As quantum dots embedded in GaAs using advanced transmission electron microscopy

Abstract: Energy relaxation dynamics in vertically coupled multi-stacked InAs/GaAs quantum dots Applied Physics Letters 110, 033107 (2017); 10.1063/1.4974221 High saturation intensity in InAs/GaAs quantum dot solar cells and impact on the realization of the intermediate band concept at room-temperature Applied Physics Letters 110, 061107 (2017); 10.1063/1.4975478 Stress-determined nucleation sites above GaAs-capped arrays of InAs quantum dots

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 26 publications
2
30
0
1
Order By: Relevance
“…The experimental data presented above reveal considerable changes in the intensity and spectral shape of the PL from InAs QDs when overgrown by GaAs at low temperature. This fact is, in general, consistent with TEM study of a similar InAs QD, which showed the GaAs overgrowth process making changes in the InAs QD shape and chemical composition. In order to make this statement more specific let us compare the overgrowth procedures for the samples.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The experimental data presented above reveal considerable changes in the intensity and spectral shape of the PL from InAs QDs when overgrown by GaAs at low temperature. This fact is, in general, consistent with TEM study of a similar InAs QD, which showed the GaAs overgrowth process making changes in the InAs QD shape and chemical composition. In order to make this statement more specific let us compare the overgrowth procedures for the samples.…”
Section: Discussionsupporting
confidence: 89%
“…The approximate calculation results were then justified by numerical solution of the Schrödinger equation for 3D pyramidal InAs QD surrounded by GaAs. The precise geometry and In distribution in the QDs were taken from previous microscopical study . Strain in the InAs/GaAs system was taken into account as described in ref.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of strain on the carrier confinement due to the lattice mismatch between InAs and GaAs materials is also taken into account for the calculation [20]. Hydrostatic and uniaxial strains are given by the following expressions: ϵh=ϵxx+ϵyy+ϵzz and ϵb=ϵzz12(ϵxx+ϵyy) where ε b , ε h are hydrostatics and uniaxial strain respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This effect has been described theoretically in Refs. [19][20][21]23, and 24 as well as demonstrated by many growth experiments; 1,2,22,25,26 however, it has not been measured or shown directly so far.…”
mentioning
confidence: 93%